Cote d'Ivoire : Fourth Reviews Under the Arrangement Under the Extended Credit Facility and Under the Extended Arrangement Under the Extended Fund Facility, and Request for Modification of Performance Criteria-Press Release; Staff Report; Debt Sustainability Analysis; Supplementary Information; and Statement by the Executive Director for Cote d'Ivoire. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
The ruling party won about half of the seats in the October 2018 municipal elections, but the political landscape is becoming more complex and uncertain, with the competition among the three traditional parties intensifying ahead of the 2020 presidential elections. The economic outlook remains strong, underpinned by robust consumption and investment, but risks are tilted downside. Growth is projected to stay around 7 1\2 percent in 2018-19. Inflation is expected to remain subdued.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Cote d'Ivoire